2014
DOI: 10.1017/s0031182014001474
|View full text |Cite
|
Sign up to set email alerts
|

The protozoan parasiteTrichomonas gallinaecauses adult and nestling mortality in a declining population of European Turtle Doves,Streptopelia turtur

Abstract: 23SG19 2DL, UK. +44 (0)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 40 publications
2
59
2
Order By: Relevance
“…The positive associations between turtle dove condition and the proportion of fed, cultivated and brassica taxonomic units in the diet of adult turtle doves suggest that anthropogenic food makes up for a shortfall in availability of other food resources, especially prior to the onset of breeding (when adult birds were sampled). The addition of wild bird seed mixes to turtle dove diet may have had further consequences, with the possibility of increased exposure to parasites such as Trichomonas gallinae (Stockdale et al., ), a parasite transmitted at shared food and water resources (Stabler, ), linked to feeding on resources commonly shared with other species (Lennon et al., ). However, the negative relationship between fed and brassica dietary components and nestling condition, and positive association with natural dietary components, suggests that reproductive success is still reliant upon the availability of natural food resources.…”
Section: Discussionmentioning
confidence: 99%
“…The positive associations between turtle dove condition and the proportion of fed, cultivated and brassica taxonomic units in the diet of adult turtle doves suggest that anthropogenic food makes up for a shortfall in availability of other food resources, especially prior to the onset of breeding (when adult birds were sampled). The addition of wild bird seed mixes to turtle dove diet may have had further consequences, with the possibility of increased exposure to parasites such as Trichomonas gallinae (Stockdale et al., ), a parasite transmitted at shared food and water resources (Stabler, ), linked to feeding on resources commonly shared with other species (Lennon et al., ). However, the negative relationship between fed and brassica dietary components and nestling condition, and positive association with natural dietary components, suggests that reproductive success is still reliant upon the availability of natural food resources.…”
Section: Discussionmentioning
confidence: 99%
“…The avian influenza is a striking example, because feral water birds form the natural reservoir of these viruses474849. During the last decade, several investigations of feral birds have pointed at the increased disease risk by immunosuppression, which is also reflected in altered disease dynamics35051525354.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of Turtle-doves in Britain (Lennon et al, 2013;Stockdale et al, 2015) have shown that the protozoan parasite Trichomonas gallinae causes mortality of adults and chicks. For this reason, identifying and studying the sources and prevalence of parasitic diseases is of great importance, not only in North Africa, but in all countries frequented by the Turtle-dove.…”
Section: Parasites and Disease Researchmentioning
confidence: 99%